Age-specific waist circumference cutoff-points for abdominal obesity diagnosis: a personalized strategy for a large Venezuelan population (2021)
Background Evidence shows that the ageing process is a determining factor in fat distribution, composition, and functionality. The goal of this research was to determine cut-off points for waist circumference according to age in the adult population from Maracaibo city, Venezuela. Methodology The Metabolic Syndrome Prevalence Study is a descriptive, cross-sectional study with multi-stage randomized sampling. In this post-hoc analysis 1902 individuals ≥18 years and from both sexes were evaluated. Waist circumference ROC curves were built for each age group and sex, using metabolic phenotypes for classification. Results 52.2% (n = 992) were women, and the mean age was 38.7 ± 2. Cut-off points obtained for the <30 years age group were: 91 cm for women (Sensitivity: 96,8%, Specificity: 97,7%) and 94 cm for men (Sensitivity:100%, Specificity: 99,2%); for 30–49 years: women 94 cm (Sensitivity: 93.7%, Specificity: 97.1%) and men 95 cm (Sensitivity: 97.3%, Specificity: 100%); for ≥50 years: women 94 cm (Sensitivity: 91.8%, Specificity: 86.7%) and men 101 cm (Sensitivity: 100%, Specificity: 100%) Conclusion The use of specific cut-off points according to age groups is proposed to determine abdominal obesity in Maracaibo city due to the underestimation seen in young people and the overestimation observed in older people when using a unique cut-off point.